Collection Development in the Digital Age
DOI: 10.29085/9781856048972.003
|View full text |Cite
|
Sign up to set email alerts
|

The concept of collection development in the digital world

Abstract: The concept of collection development is central to the professional practice of librarianship as the whole notion of a library is fundamentally associated with the idea of a collection, to the extent that the words 'library' and 'collection' are almost synonymous. Other terms such as 'information centre' 'learning centre' or 'discovery centre' are often used now instead of 'library' and terms such as 'information resources' may be substituted for 'library collections', but the activities and processes traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…The authors found that patients and families increasingly used the print collection, and new items were added based on consumer requests. However, with the transition to digital technology and the integration of electronic materials and acquisition of external databases in e-libraries, collection development practices continue to evolve [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that patients and families increasingly used the print collection, and new items were added based on consumer requests. However, with the transition to digital technology and the integration of electronic materials and acquisition of external databases in e-libraries, collection development practices continue to evolve [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The situation is complicated because In order to consider these four articles through the lens of collection management, an understanding of common collection management practices is required. However, a review of the literature on collections management reveals that there is no uniform standard for this area of practice, and moreover, that the terminology itself (whether "collection development" or "collection management") is fraught (Corrall, 2012). Even so, Corrall 2012…”
Section: Editing Libguides Through Collection Management Practicesmentioning
confidence: 99%
“…In the context of the management of policies, Corrall (2012), Johnson et al (2012), Kempf (2013) and Mangrum and Pozzebon (2012) opined that the library collection includes licensed and open access information resources. The authors suggested maintaining strong library policies to ensure consistent decision making, as well as more efficient and thorough collection development of e-resources.…”
Section: Literature Reviewmentioning
confidence: 99%